2006
DOI: 10.1159/000097793
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Sensory Memory and Working Memory Processes in Children with Normal Hearing and Cochlear Implants

Abstract: There can be wide variation in the level of oral/aural language ability that prelingually hearing-impaired children develop after cochlear implantation. Automatic perceptual processing mechanisms have come under increasing scrutiny in attempts to explain this variation. Using mismatch negativity methods, this study explored associations between auditory sensory memory mechanisms and verbal working memory function in children with cochlear implants and a group of hearing controls of similar age. Whilst clear re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 115 publications
2
29
2
5
Order By: Relevance
“…Studies have identified both strengths and weaknesses in working memory (WM) and STM skills of children with hearing loss [13,14] Specifically, studies have shown deficits in digit span and non-word repetition measures and shorter verbal memory spans in children with CI [15]; [16]. More recently, Harris and colleagues compared cognitive functions in children with CI to their normal-hearing peers [12].…”
Section: Auditory (Verbal) Wm and Stmmentioning
confidence: 99%
“…Studies have identified both strengths and weaknesses in working memory (WM) and STM skills of children with hearing loss [13,14] Specifically, studies have shown deficits in digit span and non-word repetition measures and shorter verbal memory spans in children with CI [15]; [16]. More recently, Harris and colleagues compared cognitive functions in children with CI to their normal-hearing peers [12].…”
Section: Auditory (Verbal) Wm and Stmmentioning
confidence: 99%
“…Además no presentaron diferencias de la amplitud del MMN registrado ipsilateral o contralateral al implante coclear, sugiriendo que la estimulación eléctrica del nervio auditivo activa ambos hemisferios en sujetos con hipoacusia profunda bilateral 53 . También se ha estudiado el MMN en niños con sordera profunda bilateral prelingual con implante coclear (tiempo transcurrido tras el implante fue de por lo menos 45 meses), comparados con niños normales, utilizando tonos de 500 y 2500 Hz, sin encontrar diferencias significativas en la magnitud del MMN 54 . Estos trabajos muestran que el MMN en pacientes implantados es similar al que se obtiene en controles normales.…”
Section: Implante Coclearunclassified
“…Estos trabajos muestran que el MMN en pacientes implantados es similar al que se obtiene en controles normales. Sin embargo, éstos han sido realizados en pacientes implantados con buen desempeño en tareas psico-acústicas [52][53][54] . Sin embargo otros estudios han encontrado que sólo en algunos de los pacientes con implantes cocleares se puede obtener un MMN.…”
Section: Implante Coclearunclassified
“…The results showed reduced WM span in this population and that WM correlated with vocabulary use, abstract reasoning, and receptive language comprehension as well as speech perception and speech intelligibility scores. The deficits in WM span and the correlations between WM and language abilities have been repeatedly confirmed by an extended number of children who are DHH in later studies across different types of WM tasks (e.g., digit span, nonword span, competing language processing task, and sentence memory), ages, or nations (Dillon, Burkholder, Cleary, & Pisoni, 2004;Dunn & Markwardt, 1989;Engel-Yeger, Durr, & Josman, 2011;Harris, Kronenberg, Gao, Hoen, Miyamoto, & Pisoni, 2012;Houston, Beer, Bergerson, Chin, Pisoni, & Miyamoto, 2012;Ibertsoon, WillstedtSvensson, Radeborg, & Sahlen, 2008;Kronenberger, Pisoni, Henning, Colson, & Hazzard, 2011;May-Mederake, & Shehata-Dieler, 2013;Mitchell & Quittner, 1996;Pisoni & Cleary, 2003;Pisoni, Kronenberger, Roman & Geers, 2011;Watson, Titterington, Henry, & Toner, 2007;Willstedt-Svensson, Loefqvist, Almqvist, & Sahlen, 2004).…”
Section: Children Who Are Dhh Language and Executive Functionsmentioning
confidence: 99%